Web accessibility in Spanish city councils: a challenge for the democratic inclusion and well-being of citizens - Elena Fernández-Díaz; Carmen Jambrino-Maldonado; Patricia P. Iglesias-Sánchez; Carlos de las Heras-Pedrosa (Humanities & Social Sciences Communications, 2023)
Abstract Public institutions find an open window and greater transparency towards citizens in the digital sphere. So much so that the websites of local corporations can be considered an instrument of democratic inclusion and overall well-being. However, web accessibility continues to be a pending issue in order to encourage any person, regardless of their physical, mental or age capabilities, to interact without any kind of barrier. This paper analyses the web accessibility of 18 provincial capital city councils in Spain, comparing two periods to detect compliance with the requirements of adaptation to citizenship by applying the Web Content Accessibility Guidelines. The results show that accessibility to the websites of local corporations is still an unresolved issue. The commitment to web accessibility is not related to the size of cities or their budgetary level. It is necessary to undertake the appropriate improvements if they want, in their commitment to all citizens, to not leave out two key groups: people with functional diversity and the elderly. The contribution of this work goes beyond the need to use a type of analysis model to evaluate the democratisation of websites as digital public services and, consequently, it raises a series of practical implications relevant to the political decision-making bodies of local councils.